2023
DOI: 10.3390/plants12040831
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar on the Fluorescence Spectra of Water-Soluble Organic Matter in Black Soil Profile after Application for Six Years

Abstract: At present, extracting water-soluble organic matter (WSOM) from agricultural organic waste is primarily used to evaluate soil organic matter content in farmland. However, only a few studies have focused on its vertical behavior in the soil profile. This study aims to clarify the three-dimensional fluorescence spectrum characteristics of the WSOM samples in 0–60 cm black soil profile before and after different chemical fertilizer treatments after six years of fertilization. Fluorescence spectroscopy combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Biochar application can promote humus formation during composting by modulating the speci c metabolic characteristics of the microbiome (Liu et al 2023), accelerate soil humi cation (Jin et al 2023), enhance the aliphatic characteristics of soil HA and reduce the proportion of aromatic structure of HA (Wang et al 2023). Wang et al (Wang et al 2014) showed that the addition of 3% biochar improver to pig manure composting promoted the process of compost humi cation and the synthesis of humic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Biochar application can promote humus formation during composting by modulating the speci c metabolic characteristics of the microbiome (Liu et al 2023), accelerate soil humi cation (Jin et al 2023), enhance the aliphatic characteristics of soil HA and reduce the proportion of aromatic structure of HA (Wang et al 2023). Wang et al (Wang et al 2014) showed that the addition of 3% biochar improver to pig manure composting promoted the process of compost humi cation and the synthesis of humic acid.…”
Section: Introductionmentioning
confidence: 99%